Challenging confinement: mass incarceration and the fight for equality in women's prisons - Ernst, Bonnie L. (New York University Press, 2023)
"Challenging Confinement is an examination of how the feminist movements in the late twentieth century ignited prison protests, activism, and reform in women's prisons during the era of mass incarceration"--